WEBSITE MAKING ORGANIZATION FIKBA SLTPN 226 JAKARTA LANGUAGES USING HTML - Rafika Natalia Dewi; Irfan, SKom, MM Irfan, SKom, MM (Jurnal Sistem Informasi, 2003)
HTML or Hyper Text Markup Language is one programming language to create a homepage or website. In making this HTML document authors use the Notepad editor. HTML document has three main tags, namely , , and . Among the tags this will then be an HTML document on the organization Web site will be defined, for example we can divide a page into multiple frames, insert a picture (image), hyoertext links, and an interactive form where we can communicate with visitors. By using HTML will provide convenience for the user in making a website. Due to HTML, a document can be accessed by all types of computers regardless of operating system platforms, in other words opating HTML can be used with Windows systems, Linux, UNIX, and so forth.